2020
DOI: 10.1186/s13023-019-1270-7
|View full text |Cite
|
Sign up to set email alerts
|

Etiologic spectrum of interstitial lung diseases in Chinese children older than 2 years of age

Abstract: Background: Childhood interstitial lung diseases (ILD) (chILD) refer to a rare heterogeneous group of disorders. Global collaborations have been working on the etiologies and classification scheme of chILD. With the development of medical technologies, some new diseases were identified to be associated with chILD and its etiologic spectrum is expanding. The aim of this study is to describe the etiologic spectrum of chILD in children older than 2 years of age and summarize the approaches to diagnosis of chILD. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 35 publications
2
10
0
Order By: Relevance
“…Furthermore, among systemic disease associated ILD, most of etiologies was connective tissue disease. This result was similar to the previous report by Tang et al ( 5 ) presenting with the common causes of systemic disease associated ILD, alveolar structure disorder associated ILD and exposure related ILD. These studies also indicated that HRCT may also reflect the presence of ILD and disease composition of ChILD.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, among systemic disease associated ILD, most of etiologies was connective tissue disease. This result was similar to the previous report by Tang et al ( 5 ) presenting with the common causes of systemic disease associated ILD, alveolar structure disorder associated ILD and exposure related ILD. These studies also indicated that HRCT may also reflect the presence of ILD and disease composition of ChILD.…”
Section: Discussionsupporting
confidence: 93%
“…A study in children with ILD (age > 2 years) showed that genetic tests contributed to 15% of the diagnoses, which was slightly better than the contribution of lung biopsies (13.5%) to the diagnosis, without having the risk associated with the surgical procedure. 23 In a pilot study for multidisciplinary team discussion on inherited pulmonary fibrosis in 95 subjects, discussion of the combined clinical, familial and genetic findings of patients resulted in a modification of the diagnosis in 10% of cases. While histology was only available in 23% of patients, performing an additional surgical lung biopsy was only proposed for four patients.…”
Section: Discussionmentioning
confidence: 99%
“…ABCA3 mutations-related ILDs have been described in cases of chILD surviving into adulthood and in adults [ 79 , 80 , 105 , 106 , 107 ]. The radiological imaging patterns conform more often to unclassifiable ILD with reticular abnormalities, ground glass opacities and scattered cystic lesions and may lead to the decision for lung biopsy, often disclosing a UIP pattern and in some association with non-specific or desquamative interstitial pneumonitis pattern or even pulmonary alveolar proteinosis (PAP)-like histology [ 108 , 109 , 110 ]. The major clinical implication so far described in SRG mutations relates to the high frequency (37%) of lung carcinoma (mostly of the adenocarcinoma type) alone (12%) or in combination with pulmonary fibrosis (25%) in SFTPA1/SFTPA2 adult carriers.…”
Section: Clinical Implications Of Carriership Of Srg ...mentioning
confidence: 99%